2021
DOI: 10.3390/cancers14010134
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives for Eye-Sparing Treatment Strategies in Primary Uveal Melanoma

Abstract: Uveal melanoma is the most common intraocular malignancy and arises from melanocytes in the choroid, ciliary body, or iris. The current eye-sparing treatment options include surgical treatment, plaque brachytherapy, proton beam radiotherapy, stereotactic photon radiotherapy, or photodynamic therapy. However, the efficacy of these methods is still unsatisfactory. This article reviews several possible new treatment options and their potential advantages in treating localized uveal melanoma. These methods may be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 132 publications
0
15
0
Order By: Relevance
“…HIFU can be used to quickly heat up a local area to temperatures above 56 C, leading to coagulation necrosis without affecting the tissue vascular system. 79 HIFU has been clinically used to treat malignancies such as hepatocellular carcinoma and prostate cancer. 80,81 However, to treat malignancies of the eye, HIFU beams would need to function at a frequency of >10 MHz.…”
Section: Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…HIFU can be used to quickly heat up a local area to temperatures above 56 C, leading to coagulation necrosis without affecting the tissue vascular system. 79 HIFU has been clinically used to treat malignancies such as hepatocellular carcinoma and prostate cancer. 80,81 However, to treat malignancies of the eye, HIFU beams would need to function at a frequency of >10 MHz.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…Iontophoresis is a technique using a low-intensity electric current to increase the biodistribution of ionized drugs, including antimetabolites like bleomycin and carboplatin. 79 One study showed a dose-dependent inhibition of neuroblastoma in mice using iontophoresis of carboplatin, without any corneal toxicity at doses under 10mg/mL. 83 Levels of carboplatin in the retina, choroid, vitreous humor, and optic nerve were higher following iontophoretic administration compared to intravenous.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…Older age at the time of diagnosis [42] and the male gender are also associated with an unfavorable prognosis [16,43]. Due to poor prognosis and limited treatment options in localized and advanced diseases, accurate diagnosis is critical in this group of patients [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Uveal melanoma (UM) is a rare ocular malignant tumor with a rapidly increasing incidence worldwide ( 4 ). The current eye-sparing treatment options include surgical treatment, plaque brachytherapy, proton beam radiotherapy, stereotactic photon radiotherapy, or photodynamic therapy ( 5 ). Even with successful local treatment of primary tumors, more than 50% of UM patients will develop metastatic diseases ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%